Nitrous oxide emissions: measurements in corn and simulations at field and regional scale - Arango Argoti, Miguel Andres (Kansas State University, 2013)
Nitrogen is critical for plant growth and is a major cost of inputs in production agriculture. Too much nitrogen (N) is also an environmental concern. Agricultural soils account for 85% of anthropogenic N₂O which is a major greenhouse gas. Management strategies for N fertilization and tillage are necessary for enhancing N use efficiency and reducing negative impacts of N to the environment. The different management practices induce changes in substrate availability for microbial activity that may result in increasing or reducing net N₂O emitted from soils. The objectives of this research were to (1) integrate results from field studies to evaluate the effect of different management strategies on N₂O emissions using a meta-analysis, (2) quantify N₂O-N emissions under no-tillage (NT) and tilled (T) agricultural systems and the effect of different N source and placements, (3) perform sensitivity analysis, calibration and validation of the Denitrification Decomposition (DNDC) model for N₂O emissions, and (4) analyze future scenarios of precipitation and temperature to evaluate the potential effects of climate change on N₂O emissions from agro-ecosystems in Kansas. Based on the meta-analysis there was no significant effect of broadcast and banded N placement. Synthetic N fertilizer usually had higher N₂O emission than organic N fertilizer. Crops with high N inputs as well as clay soils had higher N₂O fluxes. No-till and conventional till did not have significant differences regarding N₂O emissions. In the field study, N₂O-N emissions were not significantly different between tillage systems and N source. The banded N application generally had higher emissions than broadcasted N. Slow release N fertilizer as well as split N applications reduced N₂O flux without affecting yield. Simulations of N₂O emissions were more sensitive to changes in soil parameters such as pH, soil organic carbon (SOC), field capacity (FIELD) and bulk density (BD), with pH and SOC as the most sensitive parameters. The N₂O simulations performed using Denitrification Decomposition model on till (Urea) had higher model efficiency followed by no-till (compost), no-till (urea) and till (compost). At the regional level, changes in climate (precipitation and temperature) increased N₂O emission from agricultural soils in Kansas. The conversion from T to NT reduced N₂O emissions in crops under present conditions as well as under future climatic conditions.
Keywords: Nitrous oxide; Soils; Climate change; Crops; Agronomy (0285); Environmental Sciences (0768); Soil Sciences (0481)